Evidence of historical isolation and genetic structuring among broadnose sevengill sharks (Notorynchus cepedianus) from the world’s major oceanic regions - Schmidt Roach, Alice C. J. (2021)
Cosmopolitan marine pelagic species display variable patterns of population connectivity among the world’s major oceans. While this information is crucial for informing management, information is lacking for many ecologically important species, including apex predators. In this study we examine patterns of genetic structure in the broadnose sevengill shark, Notorynchus cepedianus across its global distribution. We estimate patterns of connectivity among broadnose sevengill shark populations from three major oceanic regions (South Atlantic, Oceania and Eastern Pacific) by contrasting mitochondrial and nuclear DNA haplotype frequencies. We also produced time calibrated Bayesian Inference phylogenetic reconstructions to analyses global phylogeographic patterns and estimate divergence times among distinctive shark lineages. Our results demonstrate significant genetic differentiation among oceanic regions (ΦST = 0.9789, P < 0.0001) and a lack of genetic structuring within regions (ΦST = − 0.007; P = 0.479). Time calibrated Bayesian Inference phylogenetic reconstructions indicate that the observed patterns of genetic structure among oceanic regions are historical, with regional populations estimated to have diverged from a common ancestor during the early to mid-Pleistocene. Our results indicate significant genetic structuring and a lack of gene flow among broadnose sevengill shark populations from the South Atlantic, Oceania and Eastern Pacific regions. Evidence of deep lineage divergences coinciding with the early to mid-Pleistocene suggests historical glacial cycling has contributed to the vicariant divergence of broadnose sevengill shark populations from different ocean basins. These finding will help inform global management of broadnose sevengill shark populations, and provides new insights into historical and contemporary evolutionary processes shaping populations of this ecologically important apex predator.